The Effect of Applying The Brainstorming Strategy on Creative Thinking In Mathematics Among Sixth-Grade Primary School Students (Journal of the College of Basic Education, 2025)
Despite the importance of mathematics, many students do not like this subject and suffer from difficulty understanding it. Perhaps the reason for this is the teaching methods used that provide ready-made information without exhausting the student’s creativity in thinking. Therefore, modern strategies must be used that help expand the circle of his thinking, and this is what prompted the researcher to The aim of the current research is to determine the effect of using the brainstorming strategy on creative thinking in mathematics among sixth-grade primary school students. To achieve this goal, the researcher developed the following null hypothesis.There is "no statistically significant difference at the significance level of 0.05 between the average scores of the students in the experimental group who They studied according to the brainstorming strategy, and among the students of the control group who studied according to the usual method in the creative thinking test", the research population was limited to the students of the sixth grade of primary school, the General Directorate of Education of Baghdad, Al-Karkh III, for the academic year. 2022-2023 The research sample consisted of 80 male and female students, distributed between two groups according to 40 students in the experimental group and 40 students in the control group. The researcher chose an experimental design to partially control one experimental variable, which is the brainstorming strategy, and one dependent variable, which is creative thinking. The researcher rewarded the two research groups with some variables, research requested a tool to measure the dependent variable, creative thinking, so she prepared a test for creative thinking, the number of which included 10 essay paragraphs. To verify the research hypothesis, the researcher used some statistical methods, including the difficulty coefficient for the essay paragraphs, the discrimination coefficient for the essay paragraphs, and the Cronbach alpha equation to find the stability coefficient for the paragraphs. The essay test for creative thinking and the t-test for two independent samples. As for the most important results reached by the current research, there "was a statistically significant difference at a significance level of 0.05 between the average scores of the experimental group who studied according to the brainstorming strategy and the average scores of the control group who studied according to the usual method in Testing creative thinking for the benefit of the experimental group". In light of the research results, the researcher presented some recommendations, including the necessity of activating the brainstorming strategy in teaching thinking in mathematics for the sixth grade of primary school, due to its impact on developing creative thinking skills and the necessity of holding training courses for teachers on the brainstorming strategy and paying attention to levels. Higher-order thinking in mathematics education.